PENGARUH FREKUENSI PEMUTARAN DAN PEMBILASAN DENGAN LARUTAN DESINFEKTANTERHADAP DAYA TETAS, MORTALITAS DAN BOBOT TETAS AYAM ARAB - Rohmad -; Sofana Fitri (Jurnal Ilmiah Fillia Cendekia, 2016)
Arabic chicken had many features apart from high egg production, this chicken was not incubate their egg, so their meat can be used. The purpose of this research was to find the effect of screening frequency and washing with disinfectant solution to hatchability, mortality and egg weight. Method was used in this reseach was Completely Randomized Design with 4x3 factorial pattern. The result of this research were screening frequency significantly effect on hatchability and mortality of arabic chicken, washing with disinfectant solution significantly affect on egg weight. However, interaction between screening frequency and washing with disinfectant solution give no effect on hatchability, mortality and egg weight.